A New Training Workshop for Students' IELTS Exam Mastering - Rimma Ivanova; Andrey Ivanov; Mariya Lyashenko (National Research University Higher School of Economics, 2017)
The paper is devoted to the problem of improving written communication skills in the university. It is intended to underline the importance of mastering writing skills when teaching a foreign language. Much attention is paid to teaching experience and approaches for students' mastering of the IELTS (International English Language Testing System) exam. This article is intended to fill the gaps in methodological and pedagogical aspects of teaching description of visual information materials in English. The authors worked out and implemented a new training workshop which is aimed at teaching and practicing graph description of visual information. Based on the curriculum a new syllabus has been drafted that provides further distribution of thematic, lexical and grammatical material given the specific nature of graphical material. The authors propose a two-stage teaching approach and methodological algorithm about how to work out exam strategies and form the required exam competences. The article highlights the outcomes and the challenges that are likely to arise when implementing the approach suggested by the authors. The proposed methodology can be used as a part of general foreign language training.